Zmiany w handlu zagranicznym Polski produktami rolno-spożywczymi w latach 1990-2006 - Stańko, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Between 1990 and 2006 increasing tendencies in the foreign trade of agri-food products prevailed. Polish accession to the EU caused a rapid growth of foreign trade turnover. The export growth rate was higher than the growth rate of import, which increased the surplus in the agri-food trade balance. The share of primary products in the total imports of agricultural products has grown and in the total exports has decreased. Since 1993 Poland has been a net importer of primary agricultural products and since 2000 a net exporter of processed products. In 2006 three fourth of Polish exports were destined for, and above two thirds of imports originated from the EU market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 267-273